Metabolic trade-offs associated with homeostatic adjustments in pelagic and benthic cephalopods: Comparative evaluations of NH4+/H+ transport machinery in gills - Lin, Meng-Wei; Kuan, Pou-Long; Sung, Po-Hsuan; Tseng, Yung-Che (Frontiers in Marine Science, 2022)
Cephalopods are ancient mollusks that can be found in many different ecological niches in the ocean ranging from the intertidal zone to the deep-sea abyss. In order to adapt to a lifestyle in various habitats, cephalopods have evolved a variety of locomotory modes to accommodate their respective habitats. Most cephalopods have relatively high metabolic rates due to their less efficient swimming mode by jet propulsion. This lifestyle is characterized by a high level of energy expenditure, fueled exclusively by protein diets that are rapidly digested and may produce metabolic nitrogenous waste NH3/NH4 +accumulation and acid-base disturbances. This study observed that the NH4 +transport rate in pelagic bigfin reef squid (Sepioteuthis lessoniana) is two times faster than benthic common octopus (Octopus vulgaris). Inhibition of Na+/H+ exchangers (NHEs) showed significant disruption of NH4 + and H+ excretory processes in gills of octopus but not in squid. However, inhibition of vacuolar-type H+-ATPase (VHA) significantly disrupts NH4 + and H+ transport rates in gills of both animals. Accordingly, for NH4 + and H+ homeostasis, benthic octopus with lower aerobic respiration rates utilize both active and Na+-driven secondary transport machinery. In order to avoid NH4 + accumulated in the blood, pelagic squids with higher aerobic respiration rates prefer active NH4 + and H+ transport mechanisms that consume ATP intensively.